Question

solution Let ( A=left[begin{array}{rr}4 & 6 -3 & 7end{array}right] ) and ( B=left[begin{array}{rr}3 & -6 5 & -8end{array}right] )
Then, the given matrix equation is ( X+A=B ).
[
begin{array}{rr}
therefore quad X+A=B Rightarrow X & =B+(-A)
& =left[begin{array}{rr}
3 & -6
5 & -8
end{array}right]+left[begin{array}{rr}
-4 & -6
3 & -7
end{array}right]
& =left[begin{array}{cc}
3+(-4) & -6+(-6)
5+3 & -8+(-7)
end{array}right]=left[begin{array}{rr}
-1
8 & -0
-12 &
end{array}right]
end{array}
]

# EXAMPLE 5 Find a matrix X, if X + 4 67 53 67 -3 717 5 -8 |

Solution